2022
DOI: 10.1039/d1qo01446c
|View full text |Cite
|
Sign up to set email alerts
|

2-Pyridinylmethyl borrowing: base-promoted C-alkylation of (pyridin-2-yl)-methyl alcohols with ketones via cleavage of unstrained C(sp3)–C(sp3) bonds

Abstract: 2-Pyridinylmethyl Borrowing: Transition-metal-free 2-pyridinylmethyl borrowing C-alkylation of alcohols access to ketones is developed. This unstrained C(sp3)–C(sp3) bonds cleavage of unactivated alcohols avoids the use of transition metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…1,3-Diphenyl-4-(pyridin-2-yl)butan-1-one (3a). 11 The title compound was prepared according to procedure B as described. Silica gel flash column chromatography was performed using hexanes and ethyl acetate (10:1), resulting in 21.2 mg of a colorless solid in a 70% yield, mp: 89−90 °C.…”
Section: 33-trimethyl-1-(6-methylpyridin-2-yl)butan-2-ol (4amentioning
confidence: 99%
See 1 more Smart Citation
“…1,3-Diphenyl-4-(pyridin-2-yl)butan-1-one (3a). 11 The title compound was prepared according to procedure B as described. Silica gel flash column chromatography was performed using hexanes and ethyl acetate (10:1), resulting in 21.2 mg of a colorless solid in a 70% yield, mp: 89−90 °C.…”
Section: 33-trimethyl-1-(6-methylpyridin-2-yl)butan-2-ol (4amentioning
confidence: 99%
“…Recently, we developed the methylene borrowing reaction between alcohols and ketones under transition-metal-free conditions, although the necessity of stoichiometric base and harsh reaction conditions significantly limited the substrate scope. Inspired by our previous works on the transition-metal-catalyzed β-carbon elimination of alcohols and catalytic methylene migration and transfer, we designed the transition-metal-catalyzed aza-benzyl transfer Michael addition via C–C bond cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent simplicity of the OH functional group that defines the alcohols, and specially its natural origin for the primary alcohols, [1][2][3][4] hides somewhat the complexity of the synthesis of secondary and tertiary alcohols. Their importance in drug synthesis [5][6][7][8] motivates continued efforts towards improving their synthesis. Among the spectrum of possibilities, the reaction of aldehydes to secondary alcohols with organometallic reagents is of vital importance not only academically, but industrially.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the aforementioned contributions in 1,3-carbon migration and our long-term research on transition-metal-catalyzed C–C bond cleavage of alcohols, we revealed a ruthenium-catalyzed intramolecular 1,3-aryl migration without any extrinsic radical initiators (Scheme c). The development of this novel transformation is valuable for the following considerations: (1) the intramolecular 1,3-aryl migration without using radical initiators is scarcely described; (2) Ru­(III)-catalyzed C­(sp 3 )–C­(aryl) bond cleavage of unactivated allylic alcohols is unknown; (3) selective activation of C­(sp 3 )–C­(phenyl) over C­(sp 3 )–C­(vinyl) bonds is difficult because of the small activation energy gap in the elimination step; (4) it provides a sophisticated way to reconstruct C–C bonds of a complex fragment.…”
mentioning
confidence: 99%